Can Affirmative Action Be Cost Effective? An Experimental Examination of Price-Preference Auctions - Corns, Allan; Schotter, Andrew (American Economic Review, 1999)
Can Affirmative Action Be Cost Effective? An Experimental Examination of Price-Preference Auctions by Allan Corns and Andrew Schotter. Published in volume 89, issue 1, pages 291-305 of American Economic Review, March 1999